Economic burden of drought using the life satisfaction approach: A case study of slum dwellers in southeast Iran - Minoo Mohammadkhani; Nouzar Nakhaee; Reza Goudarzi; Mahmood Nekoei-Moghadam (PLoS ONE, 2026)
Drought is one of the most visible effects of climate change and poses significant challenges for sustainable development. Assessing the costs of drought is essential for effective policymaking, and indirect costs are likely to provide a more comprehensive estimate. This descriptive-analytical study was conducted in 2023 among households in the slum areas of Kerman, a city in southeastern Iran. Given the population’s diversity, a cluster sampling method was employed, and data were collected from 507 households through a questionnaire. The research team estimated the Ordinary Least Squares (OLS) model, the Marginal Rate of Substitution (MRS), and Willingness to Pay (WTP) using the life satisfaction approach. The results indicated that 38.42% of households identified drought as the primary reason for their migration, while 33.27% were formerly smallholder farmers or agricultural workers. Notably, farmers and ranchers reported significantly lower life satisfaction levels. The MRS for these households was −0.570, underscoring the negative impact of drought on their income. Furthermore, based on their income, their willingness to pay for drought mitigation was estimated at $1,968.98 per household, reflecting their economic constraints. Overall, the modeling results from the life satisfaction approach indicate that drought imposes a significant economic burden on households, particularly smallholders and agricultural workers. The forced migration to the slum areas of Kerman, driven by declining agricultural potential viability, has not produced stability but has instead led to ongoing economic instability and reduced life satisfaction.